DETERMINATION OF PHENOL CONTENT AND PHYSICAL TEST OF COMBINED JAMU POWDERRED GINGER (Zingiber officinale Rosc. var. rubrum), KENCUR (Kaempferia galanga L.) AND TURMERIC (Curcuma domestica Val.) - Rusita, Youstiana Dwi; Ridlo, Achmad; Nasikin, M. Ali; Wijayanti, Ayu Rizki (Journal of Local Therapy, 2024)
Abstract: Powdered herbs are in the form of fine grains ground from sifted simplicia, blended with different compositions adjusted to the function and benefits of the herb, powdered herbs are consumed by brewing with warm water. This study was to determine the organoleptic physique, pH, moisture content, weight uniformity, and phenol content of herbal medicine powder in combination with red ginger (Zingiber officinale Rosc. var. rubrum), kencur (Kaempferia galanga L.) and turmeric (Curcuma domestica Val.). The method used to measure pH was using a pH meter, the moisture content using the gravimetric method, the phenol level using the foline ciocalteau method with the standard standard of gallic acid. The organoleptic results of herbal powder are in the form of powder, the taste in composition 1 is a bit bitter, in composition 2 the typical bitterness of turmeric is a little spicy, and in composition 3 it is a bit bitter. The pH results of composition 1, 2 and 3 were 5.954, 6.088 and 6.105. The results of the moisture content of composition 1, 2 and 3 were 8.1639, 6.8732 and 8.1042 respectively. The result of the uniformity of the weight of the second composition is 15% red ginger, 40% kencur, 45% turmeric.